Performance evaluation of endoscopic ultrasonography needles: Experimental study - Yamashita, Yasunobu; ASHIDA, REIKO; Gon, Chimyon; Kuroki, Hidehiro; Yamazaki, Hirofumi; Nakahata, Akiya; Tamura, Takashi; Hatamaru, Keiichi; Itonaga, Masahiro; Kitano, Masayuki (Endoscopy International Open, 2024)
Background and study aims The relative procedural performance of needles for endoscopic ultrasound-guided fine-needle aspiration/biopsy (EUS-FNA/B) is unclear. The present study therefore compared six types of 22-gauge FNA/B needles using a bench simulator.Methods Resistance forces during needle puncture and removal, needle tip damage before and after procedure, leakage after puncture of mucinous cyst models, the shape of the puncture surface at the puncture site, amounts of samples extracted, ranges of needle deflection angles, and needle deformation after multiple procedures were compared using six types of needles.Results Maximum resistance forces during puncture and removal were highest for ProCore needles and lowest for Expect needles. None of the needles had damage after puncturing. SharkCore needles showed the highest amount of leakage, whereas FNA needles showed no leakage. The puncture tracts of FNA needles remained in the form of a flap at the puncture site, whereas FNB needles broke off the target material creating a hole. The target material removed was supplemented within the puncture needle. TopGain needles produced significantly larger samples than ProCore, EZShot3 Plus, and Expect needles. FNB needles produced larger and more core samples than FNA needles. EZShot3 Plus needles had the highest range of needle deflection angle using an elevator device and the lowest needle deformation after 20 punctures at full endoscopic angle and a full elevator.Conclusions The performance of the six needles differed in various ways. Understanding the characteristics of each needle may allow for selection of the appropriate needle for each situation.
Keywords: Endoscopic ultrasonography; Fine-needle aspiration/biopsy; Intervention EUS